1991
DOI: 10.1029/91jd00449
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of longwave radiation fluxes in atmospheres

Abstract: A technique for the computation of longwave radiative quantities using the line-by-line approach has been developed in the Soviet Union. The method has been applied to obtain fluxes and cooling rates for standard atmospheric profiles used in the Intercomparison of Radiation Codes Used in Climate Models (ICRCCM) sponsored by the World Meteorological Organization. The sensitivity of the result to changes in the vertical quadrature scheme, the angular integration, and the spectral line shape is evaluated. Fluxes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The results of calculations by the approximate method [13,14] have shown that the values of ascending fluxes up to 6 km high are calculates within an accuracy of 1-3%. The maximal deviation of ascending flux values in different climatic zones are 8-14 W/m 2 .…”
Section: Algorithm Of Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of calculations by the approximate method [13,14] have shown that the values of ascending fluxes up to 6 km high are calculates within an accuracy of 1-3%. The maximal deviation of ascending flux values in different climatic zones are 8-14 W/m 2 .…”
Section: Algorithm Of Estimationmentioning
confidence: 99%
“…For a cloudless atmosphere, we calculated ITF by atmospheric gases (Н 2 О, СО 2 , and О 3 ) and aerosol. The accuracy of the method for calculating long infrared radiation fluxes was esti mated by comparison with line by line calculations [13,14]. The respective results of a comparison between solar and thermal radiation fluxes for cloud less and clouded atmosphere are presented in [13].…”
Section: Algorithm Of Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first algorithm [ Fomin , 1994] was independently tested [ Kuntz and Hofner , 1999] and the properties of the second one based on the “linear in τ” approximation [ Wiscombe , 1976] for vertically inhomogeneous atmosphere are well known. It is also worthy of note that a large family of calculations obtained with earlier versions of FLBLM was published long ago as benchmark calculations for the validation of radiation codes being used in climate models [ Feigelson et al , 1991; Fomin and Gershanov , 1997]. Of course these calculations have been used for FKDM validation.…”
Section: Validationsmentioning
confidence: 99%
“…In doing so to allow for an actual atmosphere heterogeneity the modified scaled content approximation is considered that exploits a set of effective parameters based upon the CurtisGodson approximation. Thus in order to simulate the JR photon optical path-length from the path coordinate 1=1' towards the atmosphere top (1=0) within each Av the scaled content for each i is calculated using u(O,l')= Jp(l)dl (11) where p ( I is the scaled density (g/rn3) defined as Al (1) = I I ii g (9(l)) i (12) re P,! ) t\ e g'(O) ) and ] is the reference pressure ofthe path evaluated separately for each I by the formula like P = P(l)w'(l)dl I w'(l)dl (13) The following notation are used in expressions (1 1)-(13):L is the path length ( in km); e(l), P(l) are the temperature and pressure at current path coordinate 1, respectively; p' (1) is the actual density, and n,, f , m, are the model tunable parameters.…”
Section: Narrow-band Radiation Transfer Model Useful In Processing Ismentioning
confidence: 99%